Teachers’ Knowledge on the Implementation of the Montessori Curriculum - Liyana Sha’rani, Aimi; Mohamed, Suziyani (International Journal of Academic Research in Progressive Education and Development, 2023)
This study investigates the knowledge level of private kindergarten teachers in the Kuala Lumpur – Keramat Zone regarding the Montessori Curriculum. The Montessori Curriculum enhances children's development by focusing on the teacher and their environment. A survey research design with a qualitative approach was utilised, and a total of 284 private kindergarten teachers participated in this study. Data was collected through a questionnaire consisting of two sections: A: Demography Information and B: Teachers' Knowledge, distributed in kindergartens and through the WhatsApp application via the Google Form platform. Respondents had a month to answer the questionnaire. The data were analysed using IBM Statistical Package for Social Science (SPSS) software version 27.0, and the results revealed that the teachers have a high level of knowledge in implementing the Montessori curriculum. This finding indicates that the teachers are well-versed in the curriculum, which can aid private kindergartens in determining their teachers' level of knowledge. The teacher's curriculum knowledge will help produce meaningful teaching and learning experiences.